2023
DOI: 10.3390/met13071217
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Input on the Microstructure and Impact Toughness in Weld Metal by High-Efficiency Submerged Arc Welding

Abstract: The development of high-efficiency multi-wire submerged arc welding technology in bridge engineering has been limited due to the high mechanical performance standards required. In this paper, weld metal was obtained by welding at three different high heat inputs with the laboratory-developed high-efficiency submerged arc welding wire for bridges. The effect of changing different high heat inputs on the microstructure and impact toughness of high efficiency submerged arc weld metal was systematically investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Generally, grain refinement can improve the impact toughness [14,25,29,30]. In this study, MED was found to decrease with increasing Mo content, but rather than enhancement, the impact energy deteriorated.…”
Section: Effect Of Mo Content On the Impact Toughnessmentioning
confidence: 49%
“…Generally, grain refinement can improve the impact toughness [14,25,29,30]. In this study, MED was found to decrease with increasing Mo content, but rather than enhancement, the impact energy deteriorated.…”
Section: Effect Of Mo Content On the Impact Toughnessmentioning
confidence: 49%
“…As production demands increase, traditional welding methods can no longer meet the requirements. In contrast, high-energy welding can significantly improve welding efficiency [3], reduce the number of passes, and shorten the welding cycle due to its advantage of higher heat input [4,5]. However, the higher wire energy and slower cooling rate lead to a weakening of the lowtemperature impact properties of pressure vessel steels in the welding heat-affected zone.…”
Section: Introductionmentioning
confidence: 99%